FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STROKE PADA PASIEN DI RSUD DR.BEN MBOI - Clareta Monica Oktaviane Teja; Imelda Februati Ester Manurung; Deviabri Sakke Tira (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2022)
Stroke is a disease of the brain in the form of local and or global nerve function disorders, appearing suddenly, progressively and rapidly. Impaired nerve function in stroke is caused by non-traumatic cerebral blood circulation disorders. Based on the results of the Basic Health Research (Riskesdas) in 2018, stroke prevalence data showed an increase from 7% per 1000 population in 2013 to 10.9% per 1000 population in 2018. The purpose of this study was to analyze the factors of age, gender, history of hypertension. , history of diabetes mellitus, obesity, and smoking on the incidence of stroke in hospitalized patients at Dr. Ben Mboi. The type of research used is observational analytic with a case control research design. The number of samples was 40 cases and 40 controls. The case sample was taken using a simple random sampling technique which was taken based on data from stroke patients who were hospitalized during the period January to December 2021. The control sample was taken by matching sampling which took samples of gender and age. Data analysis was univariate and bivariate using chi square test using SPSS program. The results of bivariate analysis showed that the factor associated with the incidence of stroke was hypertension (OR= 5.74; 95% CI: 2.15 – 15.2). Meanwhile, factors that are not related to the incidence of stroke are age, gender, history of diabetes mellitus, obesity, and smoking.